Mitigation of voltage sags using dynamic voltage restorer and distribution static compensator / Mohd Padli Harun - Harun, Mohd Padli (2009)
This paper presents the techniques of mitigation the voltage sags and interruption in a distribution system. Dynamic voltage restorer (DVR) and the distribution static compensator (D-STATCOM) are used in this study. Both of these methods are based on the Voltage source Converter (VSC) principle. The DVR injects voltage in-series with the system voltage and D- STATCOM injects a current into the system to correct the voltage sag and interruption. All the mitigation techniques will be tested for different types of fault. The simulation will be using MATLAB Simulink software. Results are presented to assess the performance of each device as a potential distribution power solution.